Hubungan Metode Role Playing dengan Rasa Percaya Diri Siswa di Kelas IV SD Negeri 091254 Batu Onom dan SD Negeri 091273 Karang Bangun Kecamatan Siantar Kabupaten Simalungun - Ramiana Putri Siboro; Lisbet N. Sihombing; Eva Pasaribu (Medan Resource Center, 2022)
The purpose of the study was to determine whether there was a relationship between the role playing method and the self-confidence of students in grade IV SD Negeri 091254 Batu Onom and SD Negeri 091273 Karang Bangun, Siantar District, Simalungun Regency.This research method is a quantitative type of research with an Ex Post Facto form of research with 73 students as respondents consisting of two schools. The technique for collecting data used in this research is the questionnaire method and the documentation method. The data analysis technique in this study is the Chi Square formula (x^2). Based on the results of the research that has been obtained, from the Chi Square formula (x^2), then the next step is to interpret the value or value of the Chi Square Count (x^(2_hitung )) with the Chi Square table (x^(2_table )). With a price or db value (Degree of Validity) of 4, the Chi Square value (x^(2_table )) with a significance level of 5% = 9,488 is known then the Chi Square value (x^2) of 11.74 is declared greater than the Chi value Square of the table (x^(2_table )). It can be stated that H_0 in this study is rejected and H_a is accepted, which means that there is a significant relationship between the role playing method and the self-confidence of students in grade IV SD Negeri 091254 Batu Onom and SD Negeri 091273 Karang Bangun, Siantar District, Simalungun Regency.